Proteins, peptides, polysaccharides, and nucleotides with inhibitory activity on human immunodeficiency virus and its enzymes - Ng, Tzi Bun; Cheung, Randy Chi Fai; Wong, Jack Ho; Chan, Wai Yee (Applied microbiology and biotechnology, 2015)
Human immunodeficiency virus (HIV), the causative agent of acquired immune deficiency syndrome, has claimed innumerable lives in the past. Many biomolecules which suppress HIV replication and also other biomolecules that inhibit enzymes essential to HIV replication have been reported. Proteins including a variety of milk proteins, ribosome-inactivating proteins, ribonucleases, antifungal proteins, and trypsin inhibitors; peptides comprising cathelicidins, defensins, synthetic peptides, and others; polysaccharides and polysaccharopeptides; nucleosides, nucleotides, and ribozymes, demonstrated anti-HIV activity. In many cases, the mechanism of anti-HIV action has been elucidated. Strategies have been devised to augment the anti-HIV potency of these compounds.